"Mothers are Medicine": U.S. Indigenous Media Emphasizing Indigenous Women's Roles in COVID-19 Coverage. (July 2022) - Carter Olson, Candi S.; LaPoe, Benjamin; LaPoe, Victoria; Azocar, Cristina L.; Hazarika, Bharbi
As COVID-19 surged in 2020, non-Indigenous media had a chronic disease of its own: sparse pandemic news from Indian Country. Within this inadequate coverage, there was an erasure of sources: Indigenous women were missing. This study evaluates the role of gender in U.S. Indigenous news coverage during the early stage of the COVID-19 pandemic. In a qualitative thematic textual analysis, 161 Indigenous media news articles were analyzed to examine gendered news coverage themes from the time the United States instituted a nationwide quarantine until the autumn of 2020. U.S. Indigenous media amplified voices of the Indigenous women on the COVID-19 frontlines. This study focuses on Indigenous media as the benchmark for telling ethical diverse Indigenous community-focused stories, illustrating how women's voices led media coverage and amplified issues. U.S. tribes are often matriarchal. As Europeans wielded disease and genocide as extermination tactics on these communities, women's voices served as medicine to guide narratives to community solutions and healing. As such, this study seeks to add to current theoretical understanding of how Indigenous women's roles were portrayed in COVID-19 coverage.